Lifestyle management and compliance in coronary patients: The gender gap. Results from the ESC EORP EUROASPIRE V survey. (11th May 2021) - Vynckier, P; Gevaert, S; De Bacquer, D; De Smedt, D
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): Fonds voor hartchirurgie - Fonds pour la Chirurgie Cardiaque OnBehalf: EUROASPIRE studygroup BACKGROUND: Although previous EUROASPIRE (European Survey Of Cardiovascular Disease Prevention And Diabetes) findings suggest only limited gender differences in the medication intake of coronary patients, the CVD risk factor profile in women remains suboptimal compared to men. Therefore, to further lower the risk of subsequent cardiovascular events, lifestyle behaviour in secondary prevention is crucial. Little is known about gender differences in prescribed lifestyle and patient compliance in tackling lifestyle related risk factor targets. PURPOSE: The aim of this study is to identify gender differences in lifestyle prescription and lifestyle compliance after a coronary event. METHODS: Analyses were carried out on the ESC EORP EUROASPIRE V survey data, including information from coronary patients recruited in 27 European countries. Consecutive patients <80 years were hospitalized for a CABG, PCI, acute myocardial infarction or acute myocardial ischaemia. Information on lifestyle prescription and lifestyle compliance, were obtained from standardized patient interviews (6 months to 2 years following hospital discharge). Logistic regression analyses adjusting for medical history (stroke, heart failure and diabetes) were performed. RESULTS: Data was available for 8261 patients of which 25.8% were women. The mean (SD) age at interview was 62.9 (9.7) years for men and 65.4 (9.2) for women. Overall, no gender differences were observed in smoking cessation advice (85.2% vs. 84.5%; P = 0.90) and in smokers' attempts to quit smoking (62.6% vs. 63.9%; P= 0.58). Also, no gender differences were observed in dietary advice (85.5% vs. 84.9%; P= 0.32) and in attempts to adopt a healthier diet (87.1% vs. 88.4%; P= 0.14). In contrast, although no gender differences were seen in weight changes among obese patients (60.1% vs. 58.2%; P = 0.49), women were less likely to receive advice on losing weight (75.1% vs. 71.6%; P = 0.02). Interestingly, the latter findings were driven by educational level. Women with a low education level were less likely to receive weight loss advice (71.8% vs. 52.9%; P < 0.001) and a lower proportion of them tried to lose weight (52.3% vs. 36.7%; P < 0.001), while no significant differences were observed in those with a high educational level. Furthermore, women were less likely to receive physical activity advice (63.8% vs. 59.6%; P < 0.001) and a lower proportion of them attempted to increase their physical activity levels (55.5% vs. 48.0%; P < 0.001). CONCLUSION: These findings suggest worse lifestyle prescription and lifestyle changes for physical activity in women and worse weight loss prescription and weight loss compliance in low educated but not highly educated women. Specific attention should be given to women with a low educational level. Further quantitative and qualitative research is needed to understand the gender gap in lifestyle management.